2018
DOI: 10.1002/mgg3.497
|View full text |Cite
|
Sign up to set email alerts
|

Associations of genetic variants in endocytic trafficking of epidermal growth factor receptor super pathway with risk of nonsyndromic cleft lip with or without cleft palate

Abstract: BackgroundThe genetic etiology of nonsyndromic cleft lip with or without cleft palate (NSCL/P) has not been fully clarified to date. Epidermal growth factor receptor (EGFR) was reportedly involved in its biological establishment and regulation of cell migration during the embryonic stage.MethodsWe selected a super pathway of endocytic trafficking of EGFR and investigated the associations of single‐nucleotide polymorphisms (SNPs) in the super pathway with the risk of NSCL/P by analyzing our published genome‐wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
(48 reference statements)
1
12
0
Order By: Relevance
“…The findings supported the role of CLPTM1(3), NECTIN1 (19), OFC1 (22), SPRY2 (23), THADA (24), SHTN1 (54), NOGGIN (27), TPM1 (30), GREM1 (31), PAX7 (34), SHH (36), SIX3 (37), BRIP1(BACH1) (38), BRCA1 (40), MAFB (26), FOXE1 (42), AXIN2 (43), SNAI1 (46), BRCA2 (40), GLI2 (48), GRHL3 (49), COL21A1 (50), WNT5A (51), TOX3 (52), and SOX9 (52) in the development of a CL ± P malformative phenotype. The findings also revealed that GAD1 (28), ARHGAP29 (39), and DVL2 (43) were regulatory proteins essential for proper development of the face.…”
Section: Genes Associated With Orofacial Closure Defectssupporting
confidence: 68%
See 1 more Smart Citation
“…The findings supported the role of CLPTM1(3), NECTIN1 (19), OFC1 (22), SPRY2 (23), THADA (24), SHTN1 (54), NOGGIN (27), TPM1 (30), GREM1 (31), PAX7 (34), SHH (36), SIX3 (37), BRIP1(BACH1) (38), BRCA1 (40), MAFB (26), FOXE1 (42), AXIN2 (43), SNAI1 (46), BRCA2 (40), GLI2 (48), GRHL3 (49), COL21A1 (50), WNT5A (51), TOX3 (52), and SOX9 (52) in the development of a CL ± P malformative phenotype. The findings also revealed that GAD1 (28), ARHGAP29 (39), and DVL2 (43) were regulatory proteins essential for proper development of the face.…”
Section: Genes Associated With Orofacial Closure Defectssupporting
confidence: 68%
“…It is a proteincoding gene expressed in the proximal maxillary location that plays a role in the development of craniofacial structures, is involved in neural polarization, and contributes to axon formation, growth, and morphogenesis. SHTN1 also playes an important role in cell migration and nervous system development and is associated with the risk of NSCL/P (54).…”
Section: Genes Associated With Orofacial Closure Defectsmentioning
confidence: 99%
“…However, some previous studies have described that EGFR might be involved in cleft palate development in mice due to the fact, that EGFR-deficient mice have very high incidence of cleft palate [19]. Also, the other study from China found out that single nucleotide polymorphism in EGFR associated gene is related to nonsyndromic orofacial cleft development [20]. According to the diverse results of the studies and our results, it can be suggested that the variability of EGFR expression in cleft affected tissue may give evidence about different pathogenetic pathways of orofacial cleft development between the species, with the decreased expression of EGFR in animals.…”
Section: Discussionmentioning
confidence: 99%
“…The activity can be increased due to higher epidermal growth factor synthesis, EGFR overexpression or EGFR mutation [18]. Studies show that EGFR signalling is necessary for normal craniofacial development and palate closure, which gives an evidence that decreased activity of the receptor may lead to impaired craniofacial development and cleft formation [19,20]. EGFR is also one of the most important growth factors receptors, stimulating tissue growth and regeneration processes, and in possible conjunction with another strongest growth factor -TGF-β1is being particularly interesting in cleft patients [14,17,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Quality control of genotyping was applied as described previously. SNPs that did not satisfy the following criteria in two GWAS datasets were excluded: (i) overall genotype call rate less than 95%; (ii) minor allele frequency (MAF) <0.05; (iii) HWE p-value < 1 × 10 -4 (Li et al, 2018;Sun et al, 2015).…”
Section: Genotyping Imputation and Quality Control Of Gwas Datamentioning
confidence: 99%